2014
DOI: 10.3168/jds.2014-8128
|View full text |Cite
|
Sign up to set email alerts
|

Total milk fat extraction and quantification of polar and neutral lipids of cow, goat, and ewe milk by using a pressurized liquid system and chromatographic techniques

Abstract: Although milk polar lipids such as phospholipids and sphingolipids located in the milk fat globule membrane constitute 0.1 to 1% of the total milk fat, those lipid fractions are gaining increasing interest because of their potential beneficial effects on human health and technological properties. In this context, the accurate quantification of the milk polar lipids is crucial for comparison of different milk species, products, or dairy treatments. Although the official International Organization for Standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 29 publications
6
77
0
2
Order By: Relevance
“…Krill Oil Analysis by HPLC-ELSD, Fractionation by FC-ELSD, and Characterization of Lipid Classes Figure 1 shows the profile of lipid classes of KO analyzed by HPLC-ELSD for the separation of neutral and/or polar lipids in qualitative and quantitative conditions following the procedure described by Castro-Gomez et al (2014). The results revealed that KO was mainly composed of TAGs and PLs (43.7 and 48.9 %, respectively) and other minor compounds (Table 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Krill Oil Analysis by HPLC-ELSD, Fractionation by FC-ELSD, and Characterization of Lipid Classes Figure 1 shows the profile of lipid classes of KO analyzed by HPLC-ELSD for the separation of neutral and/or polar lipids in qualitative and quantitative conditions following the procedure described by Castro-Gomez et al (2014). The results revealed that KO was mainly composed of TAGs and PLs (43.7 and 48.9 %, respectively) and other minor compounds (Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…Samples of KO as well as the isolated KO fractions were prepared at 5 mg/mL, and the injection volume was 50 μL. Solvent gradient was as detailed in Castro-Gomez et al (2014). Analyses were carried out with solvents freshly prepared.…”
Section: Hplc-elsd Analysismentioning
confidence: 99%
“…Yogurt fat was extracted from the freeze-dried yogurt samples following the Folch method modified according to Castro-Gómez et al [47]. The fat samples were derivatized following the method described in Castro-Gómez et al [48].…”
Section: Methodsmentioning
confidence: 99%
“…However, these data have been further updated/completed by the works carried out on small ruminants' milk and some of its products by Yao et al [36], Castro-Gómez et al [37], Zancada et al [38], Contarini and Povolo [39], Rodríguez-Alcalá and Fontecha [40] (this latter also focused on powder buttermilk), and Park [41]. Moreover Barry et al [42] reported the PL composition of butter, butterserum, cream, butteroil, and whole and skimmed milk while Fong et al [43] analysed infant formulas and Ferreiro et al [44] described the evolution of PL concentration during the production of quark cheese.…”
Section: Contents and Distribution Of Polar Lipids In Dairy Productsmentioning
confidence: 99%
“…Some approaches to the development of faster methods (10 minutes) have been focused on the utilization of pressurized liquid extraction (PLE) for the isolation of milk fat from goats', ewes', and cows' milk with a dichloromethane/methanol solution (2 : 1 v/v) as solvent mixture at 10.3 MPa and 60°C [37]. These authors did not find differences between the molecular species composition of TG and the total fatty acid profile of the assayed milks by PLE or Folch's method.…”
Section: Extraction and Purification Proceduresmentioning
confidence: 99%